2012
DOI: 10.1097/htr.0b013e31823cd01f
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Examination of Prolonged Exposure Therapy With Iraq and Afghanistan Veterans With a Diagnosis of Posttraumatic Stress Disorder and Mild to Moderate Traumatic Brain Injury

Abstract: : These findings suggest that PE can be safely and effectively implemented with Veterans with PTSD, a history of mild to moderate TBI, and current cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 32 publications
3
52
2
Order By: Relevance
“…However, the combination of the present and previous findings demonstrate that patients with co-occurring PTSD, SUD, and mTBI do not present with dramatically more severe affective symptoms and no differences in alcohol use, suggesting that these patients could benefit from standard treatments for PTSD, such as Prolonged Exposure (PE; Foa, Hembree, & Rothbaum, 2007), or newer, integrated treatments for PTSD and SUD, such as Concurrent Treatment for PTSD and Substance Use Disorders Using Prolonged Exposure (COPE; Back et al 2014). In fact, preliminary data has demonstrated that PE can be used successfully to treat veterans with PTSD and mTBI (Wolf, Strom, Kehle, & Eftekhari, 2012). Additional research is needed to determine the effect of COPE on the co-occurrence of PTSD, SUD, and TBI.…”
Section: Discussionmentioning
confidence: 96%
“…However, the combination of the present and previous findings demonstrate that patients with co-occurring PTSD, SUD, and mTBI do not present with dramatically more severe affective symptoms and no differences in alcohol use, suggesting that these patients could benefit from standard treatments for PTSD, such as Prolonged Exposure (PE; Foa, Hembree, & Rothbaum, 2007), or newer, integrated treatments for PTSD and SUD, such as Concurrent Treatment for PTSD and Substance Use Disorders Using Prolonged Exposure (COPE; Back et al 2014). In fact, preliminary data has demonstrated that PE can be used successfully to treat veterans with PTSD and mTBI (Wolf, Strom, Kehle, & Eftekhari, 2012). Additional research is needed to determine the effect of COPE on the co-occurrence of PTSD, SUD, and TBI.…”
Section: Discussionmentioning
confidence: 96%
“…Preliminary studies examining the impact of CPT and PE on Veterans with PTSD and co-occurring TBI have shown promising results in reduction of symptoms. [105][106][107] It should be noted that most participants in these studies were diagnosed with mild or moderate TBI. Individuals with more severe TBI may benefit from further adjunctive treatment, such as those described in the above-mentioned studies by Chard and colleagues 105 and Walter and colleagues.…”
Section: Special Issuesmentioning
confidence: 97%
“…[7][8][9][10][11] PE demonstrates effect sizes of over 1 standard deviation improvement from baseline in intent-to-treat samples and 2 standard deviations improvement for treatment completers. 7,8,10,[12][13][14][15] Moreover, the protocol has been shown to be particularly effective in normative treatment settings for Operation Enduring Freedom (OEF)/Operation Iraqi Freedom (OIF)-related PTSD. 10,[12][13][14][15] Failing to diagnose and treat stress disorders in combat settings represents a missed opportunity, as time-limited treatment can increase functionality, 16 decrease the need for future mental health services, 17 and, in cases of ASD, prevent the subsequent onset of PTSD.…”
mentioning
confidence: 99%